Allergies, Helicobacter pylori and the continental enigmas - Sitaraman, Ramakrishnan (Frontiers in Microbiology, 2015)
Helicobacter pylori, a gastric pathogen, is known to be associated with gastric and duodenal ulcers, and is also a strong risk factor for the development of gastric cancer and lymphoma of the mucosal-associated lymphoid tissue. Ordinarily, this should make a strong case for its eradication at par with any other infectious disease. However, the unique biology of H. pylori and the complexity of its interactions with humans, its only known natural host, do not permit the recommendation of unambiguous preventive and therapeutic measures. Moreover, this organism has co-evolved with humans as a practically universal member of the natural gastric microbiota over at least 100000 years. H. pylori persists for a lifetime in mostly asymptomatic hosts, and causes clinical disease only in a minority of infections. Therefore, its potential contribution to the maintenance of human immune homeostasis, as is the case with the better-studied members of the intestinal microbiota, is certainly worthy of serious investigation. In this paper, we summarize some interesting and often anecdotal data drawn from recent studies, and examine their significance in the context of the hygiene hypothesis. We also examine whether the lower incidence of gastric cancer over large parts of the world in spite of a high prevalence of infection (the Asian and African enigmas) may be re-interpreted in terms of the hygiene hypothesis. Finally, it is suggested that an evolutionary-ecological approach to the study of H. pylori infection may help in the formulation of strategies for the management of this infection. This may well be an infectious disease wherein medical interventions may have to be personalized to ensure optimal outcomes.